Plant parasitic organisms in the rizosphere of apple trees in the Western Cape, with special reference to woolly apple aphid - Van Jaarsveld, Alwyn Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2003.